UNVEILING THE ARTISTRY OF LANGUAGE THROUGH COMPREHENSIVE EXPLORATION OF EXPRESSIVE MEANS AND STYLISTIC DEVICES - Norbekova Maftuna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstarct: Expressive Means (EM) and Stylistic Devices (SD) are fundamental elements in human communication, akin to the tools of a painter, enriching language with depth and emotion. This article explores the intricacies of EM and SD, revealing their profound impact on expressive language. EM, such as metaphors and similes, evoke vivid imagery and emotions, while SD, including alliteration and parallelism, shape linguistic style and rhythm. The intersection of EM and SD creates powerful communication, as seen in rhetorical questions employing hyperbole. Understanding these linguistic tools enhances communication skills and fosters cultural literacy, empowering individuals to navigate language with confidence. As timeless treasures of human expression, EM and SD resonate across time and culture, inspiring connection, empathy, and enlightenment.